FinTech, InsurTech, and the Regulators - Chatzara, Viktoria (InsurTech: A Legal and Regulatory View, 2020)
Considering the rapid evolution and penetration of technology in the financial sector in general, and in the insurance sector more specifically, FinTech and InsurTech respectively are destined to affect the scope and the implementation of applicable regulation. A number of issues arise: which are the value chain participants that will be ultimately subject to regulation? Who is the competent regulator from a sectoral point of view? How will the geographic scope of each national regulator’s powers be delineated, considering the global character of FinTech services? What should be the appropriate regulatory tools and methods to be applied? These issues are outlined in Sect. 1. A number of international organizations and fora are approaching and examining the FinTech/ InsurTech phenomenon, to assess its possible benefits and implications for the regulated markets. The activities undertaken by the Financial Stability Board (FSB), the Organization for Economic Co-operation and Development (OECD), and the International Association of Insurance Supervisors (IAIS) are briefly presented in Sect. 2. From a European perspective, EU authorities and institutions, including the three European Supervisory Authorities (EIOPA, EBA, and ESMA) also undertake initiatives, targeted at better comprehending the FinTech/ InsurTech phenomenon, as described in Sect. 3. Finally, there are a number of national regulators who are proactive on the national level and undertake measures aiming to foster technological innovation, in the provision of financial and insurance services, as mentioned in Sect. 4. The regulatory activity is evolving very fast. It is still in a rather preliminary phase, but a large amount of new rules is expected to be produced within the next 2 or 3 years.